Challenges of communication between the client and contractor during construction projects: the Nigerian perspective - Muktar Ishaq, Ishaq; Omar, Roshartini; Mohammed, Musa (International Institute of Academic Research and Development, 2018)
Communication today has become the crucial element of every organization. In the construction industry, during a construction project, information needs to be accurately and timely communicated among project stakeholders in order to realize the project objectives. Poor communication between clients and contractors during the construction project is one of the major factors that affect project delivery. Therefore, the purpose of this research is to investigate the causes and effects of poor communication between clients and contractors. This was achieved by identifying the causes and effects of poor communication between clients and contractors in the Nigerian construction industry through a statistical analysis. It is hypothesized that poor communication between clients and contractors, significantly affects construction projects. The population of the respondents is 150, and survey method of data collection was used. One hundred and twenty (120) questionnaires were distributed to clients and contractors in the construction industry with 80% of respondents’ rate. Several analyses such as frequency mean, ranking and Regression were used to analyze the data. The results show that, lack of cooperation and selfish interest was the most causes of poor communication between the client and contractor. Identifying barriers to communication among stakeholders in construction industry contribute in perfecting communication that result in enhancing project delivery.